Appraisal study on board diversity: Review and agenda for future research - Mahfoudh Hussein Mgammal (Cogent Business & Management, 2022)
This article aims to provide a visualization of the problems posed by board-diversity, review the latest developments in board members around the world and identify practical implications from innovative articles published in reputable-databases. By categorizing research on board-diversity to identify research gaps and trends and summarizing outcomes and explaining them based on claims in the literature. We reviewed previous literature on the findings of empirical and theoretical perspectives that support some of the claims about directors' board-diversity in shaping the corporate-governance to provide recommendations for future research. To find distinguished researches from precise literature, the time point spans from 1988 to 2021 and the articles involved in this review are from Web-of-Science. The selection criteria used the tracking keywords: "Board Diversity" and "Diversity of Board", it results with a total of 133 studies. Which are summarized and research gaps are revealed in the claims that need support through theoretical and pedagogical approaches. We are interested in what they note as one of the revised key findings, where they report that the relation between boardــdiversity and company performance is stronger in corporations that implemented reliable governance than their peers with inadequate governance. We recommend companies to appoint managers of different age groups to allow for greater diversity in values, cognitive abilities, and decision-making experience. Appointing female directors can improve board-diversity by providing a "check and balance" mechanism between different board members. The review saves writers, directors, researchers, and strategists time to research and read, by picking the most excellent and most relevant information on its own and attending it in a focused, easyــto-understand order.
Keywords: 650; board diversity; corporate governance; firm Performance; transparency; women's representation